Diagnostic Test and Management of Typhoid Fever with Family Medicine Approach: A Case Report - Glenis, Gabrielle; Darmawan Susanto, Tirta; Timotius Handoko, Marshell (Jurnal KESANS : Kesehatan dan Sains, 2024)
A 24-year-old man with fever, decreased appetite, diarrhea, anxiety, cannot do his job properly because he feels weak and feels unwell, wants to be able to recover without having to be hospitalized, suspected of having typhoid fever. The patient often forgets to wash his hands before eating, 1 month ago the patient had a cough and runny nose, influenza, typhoid, dengue, pneumonia vaccines -, 8 years ago the patient had typhoid. The patient uses online food delivery, spends more time in the hospital than at home, is a major medical profession student, history of social service to Larantuka in May, experienced changes in family circumstances in 2019 so that adaptation and maturity are needed. This journal emphasizes supporting examinations and management carried out in accordance with a holistic family medicine approach in terms of promotive, preventive, curative, and rehabilitative aspects that focus on patients, families and communities